The Development of Halal Supply Chain Research in Indonesia: A Comparative Study - Putri, Arinda Soraya; Susilo, Nazhifa Rahmi; Sakti, Ardhy Yuliawan Norma; Wicaksana, Danis Eka Prasetya (Department Industrial Engineering, University of Muhammadiyah Malang, 2024)
Halal products uphold the principles of halal throughout the entire supply chain, making managing the halal supply chain (HSC) crucial, especially for Muslim communities. Despite the importance of this topic, existing literature on halal supply chains remains limited, with most studies concentrating on the food industry. Notably, there is a significant research gap regarding the development of HSC research in Indonesia, the country with the largest Muslim population. This study aims to address this gap by conducting a comparative analysis of HSC research in Indonesia and globally. Utilizing Scopus as the data source, 355 studies on halal supply chains published between 2008 and 2024 were analyzed. A comparative study was then conducted to evaluate the development of HSC research in Indonesia based on various categories, including the number of publications, subject areas, authors, keywords, citations, paper quartiles, institutional affiliations, research objects, methods, and themes. The findings reveal that while Indonesia has made significant progress in HSC research, the research is still tiny compared to its Muslim population. These results highlight the need for further investment and focus on HSC research in Indonesia to match its global potential.